Hexagonal Boron Nitride Nanosheets Grown via Chemical Vapor Deposition for Silver Protection - Han, Rui; Khan, Majharul H.; Angeloski, Alexander; Casillas, Gilberto; Yoon, Chang Won; Sun, Xudong; Huang, Zhenguo (AMER CHEMICAL SOC, 2019)
In this study, hexagonal boron nitride nanosheets (h-BNNS)' have been grown on polycrystalline silver substrates via chemical vapor deposition (CVD) using ammonia borane as a precursor. The h-BNNS are of few-atomic-layer thickness and form continuous coverage over the whole Ag substrate. The atomically thin coating poses negligible interference to the reflectivity in the UV-visible range. The nanosheet coating also proves very effective in protecting Ag foil chemically. In contrast to bare Ag foil, the coated foil displayed only minor decolorization under high concentration of H2S. The study indicates that h-BNNS can be a promising protective coating for Ag based items such as jewelry or mirrors used in astronomical telescopes.
Keywords: CORROSION; BIOCOMPATIBILITY; NANOTUBES; COPPER; FILM; H2S; AG